Investigation of platinum-catalyzed formation of cobalt nanoparticles by mixed potential - Balela-Garcia, Mary Donnabelle L. (ASEAN engineering journal)
ICobalt (Co) nanoparticles with diameters of 20 to 60 nm were successfully formed by seed-mediated electroless deposition in aqueous solution at room temperature. The formation of Co nanoparticles was investigated by in situ monitoring of mixed potential and deposition rate. Co nanoparticles was produced when the mixed potential was below the oxidation-reduction potential of Co(II)/Co, which coincided with a sharp increase in deposited mass on a gold-sputtered quartz crystal substrate. The mixed potential was positive and Co nanoparticles were not produced without platinum (Pt) addition. Increasing concentration of Pt addition resulted in a decrease in mixed potential and Co nanoparticle diameter. Thus, Pt effectively enhanced Co deposition rate and served as nucleation seeds for Co nanoparticles.